Increasing ultraviolet light exposure is associated with reduced mortality from Clostridium difficile infection. Issue 2 (1st April 2015) - Govani, Shail M; Waljee, Akbar K; Stidham, Ryan W; Higgins, Peter DR
Abstract : Background: Clostridium difficile infection (CDI) is an increasingly common cause of inpatient mortality. Vitamin D deficiency is associated with more aggressive CDI. We aimed to determine if average annual ultraviolet light (UV) exposure was associated with mortality in patients with CDI. Methods: We used the US National Inpatient Sample (NIS) from 2004–2011 to assess the mortality risk in patients with a diagnosis of CDI (as per ICD‐9CM 008.45). Annual average state UV exposure was assigned to each hospitalization. Logistic regression was used to determine the effects of UV exposure on mortality, controlling for age, gender, race and other comorbidities. Results: During the study period, there were 2.61 million hospitalizations with a diagnosis of CDI. The mortality rate was 9.0%. In univariate analysis, the odds ratio (OR) of inpatient mortality for the UV index was 0.97 (95% CI 0.95–0.99; p  = 0.008) per unit of UV exposure. In a multivariable model adjusting for age, gender, race, Charlson‐Deyo index, season and coexisting inflammatory bowel disease, the UV index remained a protective predictor, with an OR of 0.94 (95% CI 0.92–0.96; p  < 0.001). In the multivariate model, a seasonal effect was also present, with the highest risk of inpatient mortality in the period from January to March (OR 1.11; 95% CI 1.08–1.14) and the lowest risk, from July to September (OR 0.95; 95% CI 0.92–0.98). Conclusions: An increase in UV exposure index is associated with a reduced risk of inpatient mortality in patients with CDI. A seasonal effect is also present, with the highest risk of death during winter months. Further studies exploring the role of UV light in CDI are necessary.